2011
DOI: 10.1186/1297-9716-42-88
|View full text |Cite
|
Sign up to set email alerts
|

Role of wild ruminants in the epidemiology of bluetongue virus serotypes 1, 4 and 8 in Spain

Abstract: Although the importance of wild ruminants as potential reservoirs of bluetongue virus (BTV) has been suggested, the role played by these species in the epidemiology of BT in Europe is still unclear. We carried out a serologic and virologic survey to assess the role of wild ruminants in the transmission and maintenance of BTV in Andalusia (southern Spain) between 2006 and 2010.A total of 473 out of 1339 (35.3%) wild ruminants analyzed showed antibodies against BTV by both ELISA and serum neutralization test (SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 17 publications
13
56
2
Order By: Relevance
“…Moreover, surveillance studies in red deer population have clearly suggested that adult individuals, especially males, are more susceptible to infection (García-Bocanegra et al, 2011;Ruiz-Fons et al, 2014). Although roe deer (Capreolinae subfamily) density population is equal to that of red deer, prevalence of bluetongue is significantly smaller, between 1% and 2% (García-Bocanegra et al, 2011;Corbière et al, 2012;Casaubon et al, 2013). Finally, in samples from Mouflon or Spanish ibex, Bluetongue Virus antibodies have also been detected, with a prevalence ranging from 10% to 33% (Garcia et al, 2009).…”
Section: Bluetongue Virus Infections In Wild Ruminants In Europementioning
confidence: 89%
See 2 more Smart Citations
“…Moreover, surveillance studies in red deer population have clearly suggested that adult individuals, especially males, are more susceptible to infection (García-Bocanegra et al, 2011;Ruiz-Fons et al, 2014). Although roe deer (Capreolinae subfamily) density population is equal to that of red deer, prevalence of bluetongue is significantly smaller, between 1% and 2% (García-Bocanegra et al, 2011;Corbière et al, 2012;Casaubon et al, 2013). Finally, in samples from Mouflon or Spanish ibex, Bluetongue Virus antibodies have also been detected, with a prevalence ranging from 10% to 33% (Garcia et al, 2009).…”
Section: Bluetongue Virus Infections In Wild Ruminants In Europementioning
confidence: 89%
“…As expected, the red deer aggregation during their mating season (late summer, autumn) has been found to increase significantly the susceptibility to the virus. Moreover, surveillance studies in red deer population have clearly suggested that adult individuals, especially males, are more susceptible to infection (García-Bocanegra et al, 2011;Ruiz-Fons et al, 2014). Although roe deer (Capreolinae subfamily) density population is equal to that of red deer, prevalence of bluetongue is significantly smaller, between 1% and 2% (García-Bocanegra et al, 2011;Corbière et al, 2012;Casaubon et al, 2013).…”
Section: Bluetongue Virus Infections In Wild Ruminants In Europementioning
confidence: 98%
See 1 more Smart Citation
“…Serological studies report the highest seroprevalences in red deer (up to 66.3%) and fallow deer (Dama dama; up to 50%), both belonging to the Cervinae subfamily (Corbiè re et al, 2012;García-Bocanegra et al, 2011;Linden et al, 2008Linden et al, , 2010Rossi et al, 2010Rossi et al, , 2013Ruiz-Fons et al, 2008). Roe deer were generally found sero-negative (Boadella et al, 2010;Corbiè re et al, 2012) or with sero-prevalences up to 5.1% (Linden et al, 2010;Rossi et al, 2010 and2013;Ruiz-Fons et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…Accordind to the World Organisation for Animal Health, 24 different Bluetongue virus (BTV) serotypes are spread worldwide, with little crossreactivity and crossprotection. It naturally infects the domestic and wild ruminants, particularly affecting sheep causing severe clinical disease (Maclachlan et al 2009;Noad and Roy 2009;Bréard et al 2011;García-Bocanegra et al 2011). The use of vaccines containing inactivated or attenuated virus, mono or polivalents, has been the most efficient method of controlling the disease in outbreaks and endemic regions (Gorchs and Lager 2001;OIE 2011).…”
Section: Introductionmentioning
confidence: 99%